Pre-Service Teacher Experience in Curricular Appropriation (2023)
Lesson plans in educational institutions are created according to the curriculum of each one of them, but this articulation between planning and curriculum is not always evident. In this study, the teacher-researcher used curricular appropriation to try to bridge the gap between them. This research aims to describe the actions taken by a pre-service teacher-researcher to appropriate the curriculum. Framed in the principles of the socio-critic paradigm and the teaching action-research methodology, this qualitative research used document analysis to collect information on the curricular elements of a private bilingual school in Medellín. It was also essential for the process to collect information from the teacher-researcher through strategies such as inquiring, reflexivity, and reflection. To carry out the process, 3 stages of curricular appropriation were created: (a) Facing the tree, (b) Resignifying the tree, and (c) Harvesting; these, additionally, were used to analyze the data. After developing each of the stages by the teacher-researcher, the curricular appropriation process ended up with 8 concepts that were understood as those pillars in which a lesson plan of that context should be framed. The results indicate that, to a large extent, curricular appropriation entails transforming actions, which are what lead the teacher to understand curricular appropriation through praxis.